Konsep Dasar Kerjasama Perpustakaan - Yusniah Yusniah; Nisya Siregar,; Elsa Annisa Batu Bara; Imam Azhari Hasibuan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
The library is an institution that becomes a forum for various branches of knowledge, either in the form of research results or based on human writing. In the library, there are various types of collections, which can be printed or non-printed, fiction or non-fiction. However, like any library effort to have every collection, it will not be able to be fulfilled if it is not done in collaboration with other libraries. For this reason, collaboration between libraries actually includes efforts to satisfy users in making visits to the library so that users are willing to return to visit the library. The research method used in this work is a qualitative method which was analyzed using a literature study. The results of the research will be presented in general regarding the collaboration between libraries in meeting user satisfaction. Keywords:library, cooperation, concept